Tax Credits and Asset Accumulation: Findings from the 2004 N.O.D./Harris Survey of Americans with Disabilities - Schmeling, James; Schartz, Helen A.; Morris, Michael; Blanck, Peter (Disability Studies Quarterly, 2006)
This article describes findings pertaining to the economic independence of people with disabilities from the 2004 National Organization on Disability (N.O.D.)/Harris Survey of Americans with Disabilities. The 2004 N.O.D./Harris Survey is based on information from a random sampling of 1038 adults with disabilities and 988 adults without disabilities. Economic independence is central to improving the quality of life for persons living with disabilities. It involves being employed, leveraging tax incentives, the ability to accumulate assets, including through use of financial institutions, and opportunities for home ownership. Major findings include that sampled people with and without disabilities own homes at similar rates overall, that people with disabilities are more likely to be asset poor, have fewer relationships with financial institutions, have lower rates of usage of savings accounts, have lower rates of ownership of stocks and bonds, have lower rates of holding IDAs, and make less use of the home mortgage tax deduction. The importance of asset accumulation and home ownership strategies are discussed as a means to improve economic independence, self-determination, and inclusion into society of persons with disabilities.